The Correlation between Self-Efficacy and Speaking Ability among Junior High School Students - Yana Yana; Abdul Syahid; Nurliana Nurliana (Journal of English Language and Education, 2026)
This research purpose to examine the correlation between students’ self-efficacy and their speaking ability among Junior High School. Speaking is an essential skill in learning English; however, many students still face difficulties, which may be influenced by psychological factors such as self-efficacy. This study was conducted using a quantitative methodology with a correlational design. The participants were 20 seventh-undergraduate students. Data were composed with a self-efficacy using Children’s Self-Efficacy in Learning English Questionnaire (C-SELEQ) and a speaking test using Public Speaking Test Rubric (PSCR) assessing fluency, pronunciation, vocabulary, and grammar. The data were analysed using Pearson Product Moment correlation after the normality assumption was fulfilled. The results showed that the correlation coefficient was r = -0.363 with a significance value of p = 0.115. This indicates a negative correlation between the two variables, which is not statistically significant. Therefore, the conclusions refer that, within this sample, self-efficacy does not a sufficiently valid determinant of students' speaking ability. The outcome of this research indicate that self-efficacy is not the primary factor influencing speaking ability. There are many other factors, such as the Dunning-Kruger effect, which could be one of the reasons the data is not statistically significant.